Access to Housing in Urban China - Logan, John R. (2009)
Like income inequality, housing inequality in urban China is strongly affected by state policies that give preferential treatment to insiders. In this case, the key policies are related to their residence status, which involves not only their migration history but also their legal position. Using data from the Chinese census of 2000 for eight large cities, this study shows how residence status affects access to various pathways to housing. In addition to the well-known marginal housing situation of the recent ‘floating population’, it documents surprising advantages for migrants with urban registration status and persistent disadvantages for rural migrants regardless of how long they have lived in the city.